Vendredi: wild master and divine hero - Rodrigues, Jussara da Silva (Lettres Françaises, 2009)
The novel Vendredi or Les Limbes du Pacifique by Michel Tournier retells from a new and surprising perspective one of the greatest myths of modernity: the story of Robinson Crusoe. As the title indicates, the indigenous, Friday, leaves his secondary role in the adventures of the shipwrecked to assume an important and central role in the narrative. Tournier not only constructs his character in a fascinating way but also, using parody, calls the attention to the prejudiced view turned to the primitive man characterized in the work by Daniel Defoe. Showing strong personality, Vendredi’s conception comes from the noblest sources of the history of universal literature: Greek culture and the Bildungsroman. Sources that influenced and revolutionized, each one at its time, the way man thinks about literature.